O papel da comunicação integrada de marketing na construção do valor da marca: o caso Bunge Fertilizantes - Oliveira, Elaine Ribeiro de (2011)
The role of integrated marketing communication for the construction of brand value is the main theme of this paper. In a global market perspective, companies and organizations need to amplify and open up to new horizons and new informational technologies. It shows then that in the face of diversities derived from new paradigms enforced by the contingencies in social, economical, political and cultural spheres, integrated marketing communication came to be one of the pillars for enterprize strategy and for branding management. In this context, this study approached the proposition of striving the goal of identifying the determinant factors of the role of communication in the construction of the brand value. Due to the great challenges that constantly arise in organizations regarding the uncertatinties in the global market, it was perceived that there was a necessity of working on the issue. In this situation, branding managers are looking for alteratives and strategies to work on the brand construction and adding values. A case study was adopted, focusing on Bunge Fertilizantes, an European company that leads the ranking in the agricultural fetilizers sector in Brazililian‟s agribusiness. According to the survey which was carried out, the company‟s export is currently at its pinnacle in the aforementioned sector. In this perspective, the company‟s effort in working with the brand was effectively determined, through the links of the integrated marketing communication